Shoulder Reconstruction for Brachial Plexus Birth Injuries: An In-Depth Review and Case-Based Update: Current Concept Review - Serbin, Ryan; Waters, Peter M.; Lewis, Daniel; Gaston, Glenn; Loeffler, Bryan (Journal of the Pediatric Orthopaedic Society of North America, 2023)
Brachial plexus birth injuries can result in significant shoulder dysfunction with limitations in range of motion, decreased strength, and risk of glenohumeral joint deformity. This comprehensive review examines current approaches for management of the shoulder including surgical reconstruction following these injuries. Serial clinical exams and selective imaging are critical to determine optimal timing of surgery based on recovery potential and joint pathology. For nerve reconstruction, biceps recovery is monitored monthly from birth, and if absent by 5-6 months, serves as an indication for nerve reconstruction with nerve grafting, transfers, or both. Glenohumeral contracture, deformity, and dislocation commonly occur in infancy and are assessed by exam, ultrasound, and MRI scan. Procedural intervention is indicated when there is loss of passive external rotation, active motor weakness, and/or glenohumeral deformity/dislocation present. Contracture release and joint reduction to center the humeral head on the glenoid is performed early when there are limitations in passive external rotation not resolved with therapy. Glenoid remodeling can occur when reduction is performed early (6 months to 2-3 years). Surgical options include (1) extra-articular contracture releases (e.g., botox, subscapularis slide) and closed reduction; (2) intra-articular arthroscopic/open release and reduction; and (3) contracture release/joint reduction combined with tendon transfers (latissimus-teres major most common). The lower trapezius transfer is increasingly used for active external rotation as it spares internal rotation strength and has an excellent line of pull reproducing that of the infraspinatus. For advanced joint deformity, humeral/glenoid osteotomies are utilized. A nuanced, individualized approach is required considering the child’s deficits, pathoanatomy, and age in a case-based manner. Open communication between providers and families is imperative to optimize care. Overall, this review provides a comprehensive analysis of current shoulder reconstruction approaches following brachial plexus birth injuries.